Decade-long insights: tracking asbestos-related health impacts among formerly exposed workers in Palermo, Italy - Costantino, Claudio; Ledda, Caterina; Riccò, Matteo; Costagliola, Eduardo; Balsamo, Francesco; Belluzzo, Miriam; Bonaccorso, Nicole; Carubia, Alessandro; D'Azzo, Luciano; Sciortino, Martina; Vitello, Tania; Zagra, Luigi; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Asbestos is a foremost occupational carcinogen globally. Despite the prohibition under Law 257/1992, Italy persists as one of the European nations most burdened by asbestos-related diseases (ARDs). This research assessed ARD cases in asbestos-exposed workers from the Province of Palermo, Italy, spanning 2010-2021. Methods. Data acquisition utilized the epidemiological dataset from the ‘Service of Prevention and Safety on Work Environment’ under the Prevention Department of Palermo’s Local Health Authority (LHA). Results. Between 2010 and 2021, we identified 245 ARD instances, comprising 163 Asbestosis/Pleural plaques, 41 Lung Cancers, 38 Mesotheliomas, and 3 unspecified cases. Multivariate analysis indicated a notable decline in temporal exposure for mesothelioma (HR=0.933; 95% CI=0.902-0.965) and lung cancer (HR=0.93; 95% CI=0.90-0.978) relative to pleural plaques/asbestosis. Tobacco use displayed a pronounced correlation with lung cancer (smoker HR=64.520 95% CI=13,075-318.390; former smoker HR=20.917 95% CI=4,913-89.048). A significant link was observed between mesothelioma and pleural plaques/asbestosis in those employed in shipbuilding and repair (HR=0.371 95% CI=0.155-0.892). Conclusions. ARDs persist in clinical observations, even following the 1992 cessation of asbestos-related activities, emphasizing an enduring public health challenge. Enhancing prevention strategies is paramount, focusing on amplifying anamnestic and occupational data collection, thereby facilitating superior early diagnosis strategies for these maladies in the occupationally exposed cohort.